Konsekwencje faktyczne w sądowej wykładni prawa - Łuczak, Konrad (Kwartalnik Prawa Publicznego, 2014)
This article focuses on a question of taking into account the practical consequences, by the administrative courts, in the field of the statutory interpretation. The main purpose of deliberations was to find out: (1) what kind of practical consequences were applied in particular cases, and (2) in what way courts were predicting, that such consequences will or will not occur. These two issues were examined on the basis of the division between context of inquiry and context of justification; the latter was applied.